Inclusive education: learners' perspectives on their special school placement - Taylor, Tarryn (My University, 2014)
Special schools in the South African context are seen as part of the inclusive movement, as these schools cater for and accommodate learners that have higher support needs. Although special schools often have negative connotations, as they are still perceived as a deficit approach to inclusion, such schools are alternative placements to mainstream schools, where learners with barriers to learning are accommodated, and where their specific needs are met. Little is known about how learners in special schools feel about their placement. Therefore the core objective of this research study was to ascertain how high school learners in five Johannesburg schools perceive their placement in special school settings. Five special state schools within the greater Johannesburg area consented that learners from their schools could participate in this research study. Participants from the study were randomly selected, so as to avoid stereotyping based on disability or classification. Participants were each involved in three focus group interviews, where photo diaries and written responses were used to elicit information. On completion of the three focus group interviews, each learner participated in an individual interview. The study used a qualitative approach, which was informed by the methodology of phenomenography, where the experiences of the learners, as well as the similarities and differences between the learners, were described through the collective experiences of the group. Data was analysed using aspects of grounded theory (Glaser & Strauss, 1976), where the findings of the research were presented in accordance with phenomenography, where the collective responses from the learners in terms of the separate categories were shown, underpinned by the differences and the similarities that exist between participants. The findings were reported according to five main categories, namely placement, peers, teachers, academic considerations and sport, and the data were solicited through three sub-questions that the research study posed. The findings revealed that although the majority of the learners enjoyed their placement in a special school and spoke of their experiences positively, it was evident that the establishment of separate schools that cater for learners with higher support needs intensifies the differences between learners that attend mainstream schools and those that do not. The limitations in the design and execution of the study are clarified and recommendations are provided for further research in the field. An exposition is given of the researcher’s reflection on the research, followed by concluding comments.
A research report submitted to the Faculty of Humanities, University of Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Education, Johannesburg, 2014.